Metaplastic carcinoma of the breast: a case report - Santosh, T; Rao, Epari Sanjeeva; Rao, B R Mohan (Annals of Pathology and Laboratory Medicine, 2015)
Metaplastic Carcinomas of the breast are malignant neoplasms composed of both epithelial and mesenchymal elements. The rarity of this tumor is exemplified by the fact that it accounts for only about 0.2% of all breast carcinomas. It presents histologically with diverse differentiation and the exact histogenesis of this tumor is unknown. The present case is reported for its rarity.